The surviving emotional storms programme : a service user informed programme developed from an exploratory study of help-seeking experiences of NZ tertiary students with Borderline Personality Disorder : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Auckland, New Zealand - Beckett, Jennifer Jean (Massey University, 2023)
In this qualitative thesis, 14 university students were interviewed about their lived experience of having Borderline Personality Disorder. Participants discussed arduous journeys in search of effective treatment and described their increasing risk while trying to access help, alongside their experiences when able to access publicly funded treatment. Results from thematic analysis highlighted a super-theme of a continuous invalidation loop, discussed from an ecological and attachment perspective. This started with early help-seeking invalidation in participants’ microsystems, with the loop then broadening across systems over time, and help seeking attempts. This included contact with the mental health system, which was suggested to be a perpetuating factor in the development and maintenance of Borderline Personality Disorder. The help-seeking invalidation loop was briefly interrupted when participants were diagnosed, which occurred for most, directly after a suicide attempt. Diagnosis brought temporary relief, when participants armed themselves with knowledge about the condition including prognosis and treatment. The validation from informed diagnosis aided an externalisation process to occur, enhancing connections with self and others. However, accessing treatment proved difficult, crisis and respite was perceived as invalidating and when in treatment participants’ attempts at connection were often thwarted. Results from the thematic analysis guided the design and delivery of a group intervention. The intervention was administered using an action research methodology to university students either diagnosed with Borderline Personality Disorder or with borderline traits. The intervention, an adaptation from traditional dialectic behavioural therapy, integrated the results from the thematic analysis. To address the super-theme findings, attachment theory was interspersed throughout the intervention, utilizing aspects of narrative and acceptance and commitment therapies. The intervention was adapted and evolved from participant feedback over six cycles of 12-session intervention groups. In each group participants reported reduced severity of borderline symptoms and increased mindfulness ability. The research took place prior to and during the global pandemic and Covid-19 mandatory lockdowns in NZ, during which the research was expanded to finish with an online intervention accessed by students across NZ.
Keywords: Borderline personality disorder; Treatment; College students; Mental health; Help-seeking behavior; Group psychotherapy; New Zealand; Operant behavior; 520304 Health psychology